Hubungan Regulasi Emosi dengan Self-Disclosure pada Emerging Adulthood Pengguna TikTok di Jabodetabek - Sysari Fitri Yanti; Riana Sahrani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rise of social media platforms, particularly TikTok, has contributed to increasing self-disclosure among individuals in emerging adulthood. Self-disclosure in digital public spaces is often influenced by one’s ability to regulate emotions. This study aims to examine the relationship between emotion regulation and self-disclosure among emerging adults who use TikTok in the Jabodetabek area. This research employed a quantitative approach with a survey method. A total of 305 participants aged 18–25 years, all active TikTok users who frequently upload videos, were recruited for the study. The Emotion Regulation Questionnaire (ERQ) was used to measure emotion regulation, while a self-disclosure scale adapted for social media contexts was utilized. Data analysis was conducted using Spearman’s correlation due to non-normal data distribution.The results show a significant negative relationship between emotion regulation and self-disclosure (rₛ = –0.152, p = 0.008). This indicates that individuals with higher emotion regulation tend to engage less in self-disclosure on TikTok. These findings suggest that emerging adults who are better at managing their emotions are more cautious about sharing personal information on social media. This study contributes to a deeper understanding of the psychological processes influencing social media behavior among emerging adults.